# 2023 AIME I Problems/Problem 4

## Problem

The sum of all positive integers $m$ such that $\frac{13!}{m}$ is a perfect square can be written as $2^a3^b5^c7^d11^e13^f,$ where $a,b,c,d,e,$ and $f$ are positive integers. Find $a+b+c+d+e+f.$

## Solution 1

We first rewrite $13!$ as a prime factorization, which is $2^{10}\cdot3^5\cdot5^2\cdot7\cdot11\cdot13.$

For the fraction to be a square, it needs each prime to be an even power. This means $m$ must contain $7\cdot11\cdot13$. Also, $m$ can contain any even power of $2$ up to $2^{10}$, any odd power of $3$ up to $3^{5}$, and any even power of $5$ up to $5^{2}$. The sum of $m$ is $$(2^0+2^2+2^4+2^6+2^8+2^{10})(3^1+3^3+3^5)(5^0+5^2)(7^1)(11^1)(13^1) =$$ $$1365\cdot273\cdot26\cdot7\cdot11\cdot13 = 2\cdot3^2\cdot5\cdot7^3\cdot11\cdot13^4.$$ Therefore, the answer is $1+2+1+3+1+4=\boxed{012}$.

~chem1kall

## Solution 2

The prime factorization of $13!$ is $$2^{10} \cdot 3^5 \cdot 5^2 \cdot 7 \cdot 11 \cdot 13.$$ To get $\frac{13!}{m}$ a perfect square, we must have $m = 2^{2x} \cdot 3^{1 + 2y} \cdot 5^{2z} \cdot 7 \cdot 11 \cdot 13$, where $x \in \left\{ 0, 1, \cdots , 5 \right\}$, $y \in \left\{ 0, 1, 2 \right\}$, $z \in \left\{ 0, 1 \right\}$.

Hence, the sum of all feasible $m$ is \begin{align*} \sum_{x=0}^5 \sum_{y=0}^2 \sum_{z=0}^1 2^{2x} \cdot 3^{1 + 2y} \cdot 5^{2z} \cdot 7 \cdot 11 \cdot 13 & = \left( \sum_{x=0}^5 2^{2x} \right) \left( \sum_{y=0}^2 3^{1 + 2y} \right) \left( \sum_{z=0}^1 5^{2z} \right) 7 \cdot 11 \cdot 13 \\ & = \frac{4^6 - 1}{4-1} \cdot \frac{3 \cdot \left( 9^3 - 1 \right)}{9 - 1} \cdot \frac{25^2 - 1}{25 - 1} \cdot 7 \cdot 11 \cdot 13 \\ & = 2 \cdot 3^2 \cdot 5 \cdot 7^3 \cdot 11 \cdot 13^4 . \end{align*}

Therefore, the answer is \begin{align*} 1 + 2 + 1 + 3 + 1 + 4 & = \boxed{012} . \end{align*}

~Steven Chen (Professor Chen Education Palace, www.professorchenedu.com)

## Solution 3 (Educated Guess and Engineer's Induction)

Try smaller cases. There is clearly only one $m$ that makes $\frac{2!}{m}$ a square, and this is $m=2$. Here, the sum of the exponents in the prime factorization is just $1$. Furthermore, the only $m$ that makes $\frac{3!}{m}$ a square is $m = 6 = 2^13^1$, and the sum of the exponents is $2$ here. Trying $\frac{4!}{m}$ and $\frac{5!}{m}$, the sums of the exponents are $3$ and $4$. Based on this, we (incorrectly!) conclude that, when we are given $\frac{n!}{m}$, the desired sum is $n-1$. The problem gives us $\frac{13!}{m}$, so the answer is $13-1 = \boxed{012}$.

-InsetIowa9

However!

The induction fails starting at $n = 9$ !

The actual answers $f(n)$ for small $n$ are: $0, 1, 2, 3, 4, 5, 6, 7, 7, 7, 8, 11, 12$

In general, $f(p) = f(p-1)+1$ if p is prime, $n=4,6,8$ are "lucky", and the pattern breaks down after $n=8$

-"fake" warning by oinava

## Solution 4

We have $\frac{13!}{m}=a^2$ for some integer $a$. Writing $13!$ in terms of its prime factorization, we have $$\frac{13!}{m}=\frac{2^{10}\cdot3^5\cdot5^2\cdot7^1\cdot11^1\cdot13^1}{m}=a^2.$$ For a given prime $p$, let the exponent of $p$ in the prime factorization of $m$ be $k$. Then we have $$\frac{10-2k}{2}+\frac{5-k}{2}+\frac{2-k}{2}+\frac{1-k}{2}+\frac{1-k}{2}+\frac{1-k}{2}\geq 2.$$ Simplifying the left-hand side, we get $$k\geq 4.$$ Thus, the exponent of each prime factor in $m$ is at least $4$. Also, since $13$ is prime and appears in the prime factorization of $13!$, it follows that $13$ must divide $m$.

Thus, $m$ is of the form $2^43^45^47^4\cdot11^413^{2f}$ for some nonnegative integer $f$. There are $(4+1)(4+1)(4+1)(4+1)(1+1)(2f+1)=4050(2f+1)$ such values of $m$. The sum of all possible values of $m$ is $$2^43^45^47^4\cdot11^4\sum_{f=0}^{6}13^{2f}(2f+1)=2^43^45^47^4\cdot11^4\left(\sum_{f=0}^{6}13^{2f}(2f)+\sum_{f=0}^{6}13^{2f}\right).$$ The first sum can be computed using the formula for the sum of the first $n$ squares: $$\sum_{f=0}^{6}13^{2f}(2f)=\sum_{f=0}^{6}(169)^f\cdot 2f=\frac{1}{4}\left[\left(169^7-1\right)+2\left(169^6-1\right)+3\left(169^5-1\right)+\cdots+12\left(169^1-1\right)\right].$$ Using the formula for the sum of a geometric series, we can simplify this as $$\sum_{f=0}^{6}13^{2f}(2f)=\frac{169^7-1}{4}+\frac{169^5-1}{2}+\frac{169^3-1}{4}=2613527040.$$ The second sum can be computed using the formula for the sum of a geometric series: $$\sum_{f=0}^{6}13^{2f}=110080026.$$ Thus, the sum of all possible values of $m$ is $$2^43^45^47^4\cdot11^4(2613527040+110080026)=2^33^45^37^411^413^2\cdot 29590070656,$$ so $a+b+c+d+e+f=3+4+3+4+4+2=\boxed{012}$.

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. 